The Effect of Using Augmented Reality Media in Learning Achievement Especially Psychomotor Domain at Computer Assembling Subject of X Multimedia Students in SMKN 10 Surabaya - Irfansyah, Juki; Ekohariadi, Ekohariadi; Buditjahjanto, Asto (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to determine the effect of using augmented reality media in learning achievement especially psychomotor domain at computer assembling subject of X Multimedia students in SMKN 10 Surabaya. Quasi-Experimental design has been used which consists of experimental class (augmented reality media) and control class (powerpoint slides media). Each class consists of 30 students. Data was analized by using independent sample t-test on SPSS software version 24. The data showed that psychomotor domain of the experimental class were higher than the control class.